1-stage primary arthroplasty of mechanically failed internally fixated of hip fractures with deep wound infection. (August 2013) - Klatte, Till O; O'Loughlin, Padraigh F; Citak, Mustafa; Rueger, Johannes M; Gehrke, Thorsten; Kendoff, Daniel
<x xml:space="preserve">Abstract</x> Background and purpose Mechanically failed internal fixation following hip fracture is often treated by salvage arthroplasty. If deep wound infection is present, a 2-stage procedure is often used. We have used a 1-stage procedure in infected cases, and we now report the outcome. Patients and methods We reviewed 16 cases of deep wound infection after mechanically failed hip fracture fixation, treated between 1994 and 2010. In all patients, a joint prosthesis was implanted in a 1-stage procedure. Results After an average follow-up period of 12 (2–18) years, no reinfection was detected. In 4 cases, a hip dislocation occurred and 3 of these needed further surgery. Interpretation A 1-stage procedure for arthroplasty of an infected, mechanically failed hip fracture fixation is feasible and carries a low risk of infection.